Trace element supplementation is associated with increases in fermenting bacteria in biogas mono-digestion of grass silage. (August 2019) - FitzGerald, Jamie A.; Wall, David M.; Jackson, Stephen A.; Murphy, Jerry D.; Dobson, Alan D.W.
Abstract: Trace elements (TE) are known to play a crucial role in microbial metabolism, and to improve biogas output in anaerobic digestion (AD), although the mechanisms are not well characterised. We have characterised the microbial communities associated with anaerobic mono-digestion of grass silage through initiation, stable operation, inhibition at high organic loading rates, and rescue through addition of trace elements (iron, nickel and cobalt). Comparison of these communities with communities from unsupplemented anaerobic co-digestion of a grass silage:slurry mix shows TE supplementation to be significantly associated with increases in genera known to be involved in the metabolism of volatile fatty acids ( Gelria, Anaerovorax, Dethiobacter ), hydrolysis ( Clostridia ), and in particular the uncharacterised clostridial order MBA03. However, a decrease was seen in the abundance of methanogenic Archaea, indicating TE supplementation improves mono-digestion of grass silage through augmented fermentation rather than improved methanogenesis. Highlights: Firmicute and Bacteroidetes taxa dominate in anaerobic mono-digestion of grass silage. Trace element addition associated strongly with specific acido/acetogenic species. Trace elements also associated with a general increase in fermenting Clostridia . Methanogens showed no response to trace element supplementation. Trace elements (Fe, Ni, Co) appear to supplement metabolism of acetate and propionate.